Just a sport or moral obligation? Football between pressures of politics, financial power and progress from Mussolini to Qatar - Vares Vesa (Turun korkeakoulujen yhteiskunnallis-taloudellinen tutkimusyhdistys ry, 2025)
The mantra of the sportsmen, sportswomen and politicians is that “sport and politics should not mix”. In practice, it is impossible to separate sport from political, national and economic connections, or from anything that has to do with society. Disagreements over how to define what is ”political” demonstrate this.
Today, we consider it appropriate, right, and in congruence with human values that football teams take the knee in support of the Black Lives Matter -campaign, or that the captains of the national teams are entitled to wear rainbow armbands, and we don’t consider this “political”, but a human rights issue. At the same time, authoritarian regimes have made the greatest sporting events – the Olympic Games and World Cup in football – objects of their interest, in the footsteps of Mussolini, Hitler and the leaders of the Soviet Union. The gigantically rich sheikhs and oligarchs have purchased traditional, world-famous football clubs, and the human rights situation of the migrant workers and migrants in Qatar was a highly controversial issue before the latest World Cup. Russia and Belarus were expelled from most international sport events after the Russian attack against Ukraine.
This paper deals with the history of political controversies in sports and is a part of the debate on politics in sport and economic influence on sport. It argues that the authoritarian and economic grip on sport has increased to worrying levels, but there are signs of positive development as well.ht t ps://doi.org /10.51815/f jsr.127824